Revisiting the taxonomy of Neomarica humilis (Trimezieae, Iridaceae) and some related names - Gil, André Dos Santos Bragança; Schneider, Layla Jamylle Costa; Bittrich, Volker; Amaral, Maria Do Carmo Estanislau Do (Phytotaxa, 2021)
We provide typifications and taxonomic notes for Neomarica humilis and some related species, to retain the taxonomic stability in Neomarica (Trimezieae, Iridaceae). We recognize Cypella humilis, the basionym of N. humilis, as a replacement name for the illegitimate Marica humilis, and N. vittata as a superfluous illegitimate name. We discuss the identity of the material cited by Klatt for C. humilis and designate a lectotype for M. humilis. In addition, we designate a neotype for N. occidentalis and a lectotype for N. portosecurensis. Furthermore, we distinguish N. humilis from the taxonomically related N. brachypus¸ N. northiana, and N. portosecurensis. All four species are illustrated.